2001
DOI: 10.1089/104303401753204535
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Antigen Response and Systemic T Cell Activation After In Situ Gene Therapy in Prostate Cancer Patients Failing Radiotherapy

Abstract: In an extended phase I/II study we evaluated 36 prostate cancer patients with local recurrence after radiotherapy who received single or repeated cycles of replication-deficient adenoviral vector (ADV)-mediated herpes simplex virus-thymidine kinase (HSV-tk) plus ganciclovir (GCV) in situ gene therapy with respect to serum PSA levels, alterations in immune cells, and numbers of apoptotic cells in needle biopsies. An initial cycle of HSV-tk plus GCV gene therapy caused a significant prolongation of the mean seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 21 publications
1
56
1
Order By: Relevance
“…Our previous studies using direct injection of adenoviral vectors that transduced the therapeutic HSV-tk therapeutic gene indicate that this procedure is safe and can be effectively accomplished. 35 Thus, the results of our studies suggest that an extension of this clinical protocol using IL-12-transduced DC or other gene-modified DC in a similar procedure should be pursued.…”
Section: Discussionmentioning
confidence: 89%
“…Our previous studies using direct injection of adenoviral vectors that transduced the therapeutic HSV-tk therapeutic gene indicate that this procedure is safe and can be effectively accomplished. 35 Thus, the results of our studies suggest that an extension of this clinical protocol using IL-12-transduced DC or other gene-modified DC in a similar procedure should be pursued.…”
Section: Discussionmentioning
confidence: 89%
“…8 Initial studies with a direct cytotoxic approach, HSV-tk þ GCV, suggested that in situ gene therapy could generate an immune response in experimental systems. [9][10][11] Multiple clinical trials in men with this gene therapeutic approach have revealed necrosis within prostate cancer lesions in preference to adjacent normal prostatic tissues, 12 increased immune cells 12,13 and, when combined with radiation, an increase in the frequency of biopsies without evidence of cancer. 14 Additional studies have confirmed that intraprostatic adenoviral vector-mediated HSV-tk followed by systemic GCV treatment leads to increased numbers of HLA DR þ CD8 þ T cells in the peripheral blood of treated men.…”
Section: Introductionmentioning
confidence: 99%
“…14 Additional studies have confirmed that intraprostatic adenoviral vector-mediated HSV-tk followed by systemic GCV treatment leads to increased numbers of HLA DR þ CD8 þ T cells in the peripheral blood of treated men. 13,15 We have also tested another active vaccine approach involving the immunomodulatory gene IL-12. Preclinical studies with an adenoviral vector containing the IL-12 genes (AdIL-12) in an orthotopic mouse prostate cancer model indicate that this therapy suppresses not only local tumors and also lung metastases and generates systemic immune activities such as NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several GDEPT combinations have been proposed (Springer and Niculescu-Duvaz, 1996), the most studied being the Herpes Simplex virus thymidine kinase/gancyclovir system (van Dillen et al, 2002). This combination has entered clinical trials, and shown safety and some efficacy (Sandmair et al, 2000;Miles et al, 2001).…”
mentioning
confidence: 99%